The Effect of the Implementation of Risk Management and Corporate Governance with Profit Management as a Variable Intervening on Banking Financial Performance (Analytic Study on Sharia Banking Listed on the Indonesia Stock Exchange) - Khalisah Visiana; Nyoman Rita Widianti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine whether Risk Management and Corporate Governance with earnings management as an intervening variable on the financial performance of banking companies listed on the IDX, to determine whether Risk Management and Corporate Governance affect the financial performance of banking companies listed on the IDX through earnings management as a variable. Intervening to determine whether Risk Management and Corporate Governance affect earnings management in banking companies listed on the IDX and whether earnings management affects the financial performance of banking companies listed on the IDX. The population used in this study are four banking companies listed on the Indonesia Stock Exchange. Using the purposive sampling method by the criteria, four selected banking companies are selected. Using the 2016 to 2020 observation year (5 years) to measure discretionary accrual plus the 2015 observation year, it will get 30 data observations as sampling in this study. Hypothesis testing is done by linear regression analysis. From the results of hypothesis testing, it is known that the application of risk management has no significant effect on financial performance and corporate governance has no significant effect on financial performance. Moreover, applying risk management using earnings management as an intervening variable cannot mediate financial performance. Applying corporate governance using earnings management as an intervening variable cannot mediate company performance, meaning that earnings management is not a good variable in mediating the relationship between risk management, Corporate Governance with Financial Performance (KK). Risk Management does not affect earnings management, while Corporate Governance has no effect on earnings management and earnings management has no effect on financial performance.